Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. X.home-laser (H.S. Stuttman Co, 1975)
1.393-1.546 p.; 25 cm.